School Head Instructional Supervision: Exploring its Impact on Pedagogical Innovation - Onaid, Annie Rose; Pajiji, Jocelyn; Dugasan, Nadzmin; Abdurasid, Rasul (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the influence of school head instructional supervision on pedagogical innovation at Simandagit Elementary School in Bongao, Tawi-Tawi. Anchored on Instructional Leadership Theory and Transformational Leadership Theory, the study examined how supervision practices, leadership support, and contextual conditions shaped teachers’ willingness and capacity to improve instructional practices. A qualitative phenomenological research design was employed to capture the lived experiences of the school principal and one classroom teacher. Purposive sampling was used, and data were gathered through semi-structured, in-depth interviews. The interview responses were transcribed and analyzed using thematic analysis. Findings revealed that evidence-based supervision practices, particularly the use of student performance data and classroom observations, helped guide instructional decisions and improve teaching strategies. Emotional and professional support, constructive feedback, and recognition of teacher efforts also encouraged teacher confidence, motivation, and openness to pedagogical innovation. However, the study identified time constraints, competing administrative priorities, limited instructional materials, inadequate technological tools, and limited training opportunities as barriers to the full implementation of innovative teaching practices. The study concluded that instructional supervision could promote pedagogical innovation when practiced as a supportive, developmental, and data-driven leadership process. It recommended strengthening regular classroom monitoring, timely feedback, reflective professional dialogue, institutional support for school heads, and the provision of instructional resources and training opportunities. The study supports SDG 4 – Quality Education, SDG 10 – Reduced Inequalities, and SDG 17 – Partnerships for the Goals. Its sustainability impact lies in strengthening educational, institutional, and community sustainability by promoting teacher development, instructional improvement, and equitable learning support in a resource-constrained school setting.
Keywords: Evidence-Based Supervision; Instructional Leadership; Instructional Supervision; Pedagogical Innovation; Professional Support; Resource-Constrained Schools; Teacher Development